Kinetika Adsorpsi Cangkang Telur pada Zat Warna Metilen Blue - Badriyah, Lailatul; Putri, Mardiana Prasetyani (ALCHEMY, 2017)
The analyze of reaction kinetic adsorption of methylene blue by egg shell was studied. Methylene Blue was one of the dye which used in industry applied. It was an organic compound that dangerous if it throw away in the river without prepraration yet. As a consequence would be object that could interfere biota aquatic. So, it need a treatment in liquid dye waste, that could reduce degree of dye. One of the treatment was adsorption. Egg shell shyntesized were analyzed by using FTIR. It was done to know some function groups that in. The reaction kinetic experiment was done to count in adsorption dye process, especially in the wastewater from textile industry. Dyes adsorption by using egg shell has equilibrium time at the 70 minutes after adsorption process. After that, the process has not a different significantly. The experiment data were fitted into the Langmuir and Freundlich isotherm. Both of the adsorption isoterm, the R2 value of Langmuir isotherm model was the highest, 0,9986. Having a As coeficient 0,3589 and Kb 0,7962. The adsorption kinetics of Methylene Blue on egg shell could be described by a pseudo second order model, with the regresion, R2 0,9979.